Karakteristik Fisiko-Kimia dan Sensori Mie Kering dengan Penambahan Tepung Ikan Motan (Thynnichthys thynnoides) - Riski Irsalina; Shanti Dwita Lestari; Herpandi Herpandi (Universitas Sriwijaya, 2016)
The purpose of this research was to know the physicochemical and sensory characteristics of dry noodle with minnow carp (Thynnichthys thynnoides) fish meal addition. This research used the factorial randomized block design. The treatment was different fish meal concentration (0, 5, 10, 15, and 20%). The parameters of this research were chemical variables (water, ash, lipid, protein, carbohydrate, calcium, phosphorus content), physical variables (lightness, chroma and hue, hardness, tensile strength, elongation, water absorption) and sensoric variables (colour, aroma, taste and texture). The result showed that treatment gave signitificant effect on physical variables (water, ash, lipid, protein, calcium and phosphorus content), physic variables (lightness, chroma and hue, hardness, tensile strength, elongation) and sensoric variables (colour, aroma, taste texture), but there was no significant effect on carbohydrate content and water absorption. The best treatment was addition of M1 (100% wheat flour and 5% minnows carp fish meal). The concentration of water, ash, protein, lipid, carbohydrate, calcium, and phosphorus were 13.03%, 14.21%, 23.75%, 0.9%, 46.75%, 0.127%, 0.162%, respectively. The lightness, chroma, hue, hardness, tensile strength, elongation and water absorption were 58.4%, 18.6%, 71.1o, 1011.73 gF, 15.93 gF, 27.33%, 140.98%, respectively. Panelist scores for colour, aroma, taste and texture were 3.8 (rather bright yellow), 4 (not fishy), 4.08 (tastefull) and 4.08 (chewy), respectively